PENGEMBANGAN MANAJEMEN SEKOLAH - Nurmalina, Nurmalina; Alting , M. Guntur (Cendikia: Jurnal Pendidikan dan Pengajaran, 2024)
School management is a vocational education institution that never stops improving to provide the best service to the community as a form of commitment to becoming an educational institution that produces superior graduates. The progress of the times and changes in society's demands regarding the need for a workforce that is ready and in line with the needs of the job market encourages schools to carry out various development strategies to become superior educational institutions.The development strategy implemented by the school is in the first way, strengthening human resources, namely strengthening the competence of teachers and education staff. Second, by improving school infrastructure. Third, updating the curriculum, as a form of adapting to changes and demands of the times regarding work skills. Fourth, redesign study programs and add superior study programs that suit job market needs. Fifth, carry out superior learning, by properly designing, implementing and evaluating every activity and implementation of learning carried out by referring to predetermined indicators. Sixth, Optimization of extracurricular activities to facilitate development.